A photometric study of a weak-contact binary: V873 per - Kriwattanawong,W. (Elsevier, 2015)
© 2014 Elsevier B.V. All rights reserved. We present a photometric study of a weak-contact binary V873 Per. New observations in BVR filter bands showed asymmetric light curves to be a negative type of the O'Connell effect, which can be described by magnetic activity of a cool spot on the more massive component. Our photometric solutions showed that V873 Per is a W-type with a mass ratio of q = 2.504(±0.0029), confirming the results of Samec et al. (2009). The derived contact degree was found to be f = 18.10%(±1.36%). Moreover, our analysis found the cyclic variation with the period of about 4 yr that could be due to existence of the third companion in the system or the mechanism of magnetic activity cycle in the binary. While available data indicated that the long-term orbital period tends to be stable rather than decreasing.